ANALISIS TINGKAT KEPATUHAN PASIEN TBC RAWAT JALAN TERHADAP PENGGUNAAN OBAT ANTI TUBERKULOSIS DI PUSKESMAS SINDAR RAYA - Supartiningsih Supartiningsih; RD.Siti Riski Ainun (LPPM Universitas Abdurrab, 2021)
ABSTRACT The incidence of pulmonary tuberculosis is still very high and difficult to reduce due to the lack of compliance in taking anti-tuberculosis drugs. The lack of knowledge and family support are some of the factors that affect the level of patients’ compliancein taking anti-tuberculosis drugs. The purpose of this study is to have an overview of patients’ compliance and to see how the relationship between knowledge and family support can affect TB outpatients in taking anti- tuberculosis drugs at the Sindar Raya Community Health Center. This type of research is quantitative using a cross-sectional approach to 20 respondents who do outpatient treatment at the Sindar Raya Community Center. The sampling technique uses the total sampling technique. The data collecting is done by giving questionnaires to each respondent. The data analysis uses univariate analysis and Chi Square test on bivariate analysis. The results of the univariate research showed that there were 10 respondents (50.0%) with a good level of knowledge,8 respondents (40.0%) with moderate level knowledge, and2 respondents (10.0%) with the lack of knowledge. Good family support showed as many as 9 respondents (45.0%),5 respondents (25.0%) with moderate support, and6 respondents (30.0%) with lack of support. As many as 15 respondents (75.0%) showed a good level of compliance while 5 respondents (25.0%) showed the lack of compliance level. Based on bivariate analysis with the chi square test, there was a significant relationship between knowledge and compliance to taking anti-tuberculosis drugs (P value = 0.036), and there was also a significant relationship between family support and compliance to taking anti-tuberculosis drugs (P value = 0.017).